Secrets, Plots and Semiotic Theories - Traini, Stefano (Rivista Italiana di Filosofia del Linguaggio, 2022)
Dealing with plots, conspiracies and secrets, Umberto Eco investigates those forms of reasoning that are based on the uncontrolled shift of meaning. This way, he first dwells on the historical-philosophical “precedents” of these forms of thought, describing the birth and developments of the “hermetic thought”. Then, he tries to describe the illogical shift of meanings as a pathological form of semiosis, using Peirce’s semiotic theory. He also uses the concept of connotation, defining the anomalous shift of meaning as a “connotative neoplasm”. Therefore, alongside an epistemologically-oriented semiotics (Peirce), it seems that Eco still feels the need to resort to an analysis-oriented semiotics (Hjelmslev, Barthes), despite having abandoned the structuralist paradigm for a long time, because of his philosophical propensity. Thus, moving among historical reconstructions, general philosophical theories and the application of analytical tools, Eco seems to give useful methodological suggestions for contemporary semiotics.